Synthesis of 4-phenyl-3,4-tetrahydro-indeno [2,1]-pyrimidin-2-one (LR-1) - Ritmaleni, Ritmaleni; Nurcahyani, Wahyu (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
The synthetic compound 4-phenyl-3,4-tetrahydro-indeno[2,1]- pyrimidin-2-one 20a (LR-1) was synthesised using Biginelli reaction method. The reaction involved benzaldehyde 6, 2-indanone 2 and urea 7 in acid condition. This condensation reaction yielded 15 % of the product 20, at 133,4-135,0oC of melting point and 0.15 (Et2O : CHCl3 = 1 : 3) of RfÂ value.Keywords : benzaldehyde, indenone-2, urea